Effect of girls' secondary school stipend on completed schooling, age at marriage, and age at first birth: Evidence from Bangladesh - Yeasmin Sayeed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
There are many studies on the effects of conditional cash transfer programmes on enrolment, productivity and poverty reduction but very few on causal effects on ages at marriage and first birth. And none of them considers the convergence effect. This paper provides new evidence on effects of the Female Secondary Stipend Programme in Bangladesh as an exogenous variation in time and region on schooling, ages at marriage and first birth outcomes with regression discontinuity and difference-in-difference approaches. The regression discontinuity results show that the programme increased completed years of schooling by at least 0.4 years, and delayed age at first marriage and age at first birth by at least 0.4 and 0.3 years respectively. We also show that the difference-in-difference method predicts biased results.
Keywords: D04; I21; I25; J12; 330; secondary stipend; rural girls; schooling; age at marriage; age at first birth; regression discontinuity; difference-in-difference